2011
DOI: 10.3233/jpd-2011-11058
|View full text |Cite
|
Sign up to set email alerts
|

Rab1A Over-Expression Prevents Golgi Apparatus Fragmentation and Partially Corrects Motor Deficits in an Alpha-Synuclein Based Rat Model of Parkinson's Disease

Abstract: Although the overabundance of human alpha-synuclein in nigral dopaminergic neurons is considered to play a pathogenic role in Parkinson's disease (PD), it remains unclear how alpha-synuclein leads to neuronal degeneration and motor symptoms. Here, we explored the effect of human alpha-synuclein in the rat substantia nigra following AAV-mediated gene delivery inducing a moderate loss of dopaminergic neurons together with motor impairments. A significant fraction of the surviving nigral neurons were found to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 41 publications
4
65
0
Order By: Relevance
“…The Rab proteins, small GTPases involved in membrane trafficking, play pivotal roles in the maintenance of the Golgi morphology [56]. For example, the suppression of Rab1A involved in the ER-to-Golgi trafficking, was shown to induce a fragmentation of the Golgi whereas its overexpression had the opposite effect [41, 57]. Firstly, we examined the distribution of Rab1A in primary cortical neurons by transfecting them with GFP-Rab1A construct (Fig 6A).…”
Section: Resultsmentioning
confidence: 99%
“…The Rab proteins, small GTPases involved in membrane trafficking, play pivotal roles in the maintenance of the Golgi morphology [56]. For example, the suppression of Rab1A involved in the ER-to-Golgi trafficking, was shown to induce a fragmentation of the Golgi whereas its overexpression had the opposite effect [41, 57]. Firstly, we examined the distribution of Rab1A in primary cortical neurons by transfecting them with GFP-Rab1A construct (Fig 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Our findings add another Rab GTPase to the list of possible therapeutic strategies for PD. Rab1 rescued neuron loss resulting from a-synuclein over-expression in flies (Cooper et al 2006) and partially corrected motor deficits in a rat model of PD (Coune et al 2011). Rab8 protected from a-synuclein-induced toxicity in flies (Yin et al 2014).…”
Section: Rab7 Protects From A-synuclein Toxicitymentioning
confidence: 95%
“…It was subsequently shown that α-synuclein overexpression impairs Rab1A activity and thus hinders the formation of autophagosome by interfering with Atg9 function 63 . Moreover, increased Rab1 production is sufficient to correct α-synuclein-mediated Golgi fragmentation, dopaminergic (DA) neuron loss, and motor deficits in mammalian animal models of PD 10, 11 . These observations suggest that Rab1A plays a crucial role in the pathogenesis of PD and is a potential therapeutic target for a disease currently lacking effective medicine.…”
Section: Parkinson’s Disease (Pd)mentioning
confidence: 99%